Elastic properties of (Ti,Al,Si) N nanocomposite films - Carvalho, S. (2001)
ŽTi,Al,Si.N films have been prepared by d.c. and rf reactive magnetron sputtering, with Si contents in the range 2 11 at.% and Al contents between 4 and 19 at.%. Samples prepared in rotation mode Žthree magnetrons. presented densities between 4.0 and 4.6 g cm3, while samples prepared in static mode Žmagnetron with Ti target with small pieces of Si and Al. displayed densities mainly in the range 3.0 3.9 g cm3. For comparison purposes, the evaluation of Young’s modulus was performed by both depth-sensing indentation and surface acoustic wave ŽSAW. techniques. Indentation results revealed systematically higher values than those obtained by SAW. These discrepancies might be related with the relatively low density of the films. Hardness values of approximately 60 GPa were obtained with samples with a composition of approximately 28.5 at.% titanium, 12 at.% aluminium, 9.5 at.% silicon and 50 at.% nitrogen. XRD patterns showed the presence of two different crystalline phases, as in the case of ŽTi,Si.N films. One is assigned to TiN phase Žlattice parameter of approx. 0.429 nm. and the second, the so-called solid solution which is developed in situations of low surface mobility, revealed a lattice parameter Ž0.419 nm. slightly lower than that of bulk TiN.